Teach Yourself VISUALLY iPhone 11, 11Pro, and 11 Pro Max, 5th Edition - Hart-Davis, Guy (Visual, 2020)
Know your new iPhone 11, 11 Pro, and 11 Pro Max from the inside-out with 900 color screen shots! Teach Yourself VISUALLY iPhone is your ultimate guide to getting the most out of your iPhone! Apple's graphics-driven iOS is perfect for visual learners, so this book uses a visual approach to show you everything you need to know to get up and running-and much more. Full-color screen shots walk you step-by-step through setup, customization, and everything your iPhone can do. Whether you are new to the iPhone or have just upgraded to the 11, 11 Pro, or 11 Pro Max, this book helps you discover your phone's full functionality and newest capabilities. Stay in touch by phone, text, email, FaceTime Audio or FaceTime Video calls, or social media; download and enjoy books, music, movies, and more; take, edit, and manage photos; track your health, fitness, and habits; organize your schedule, your contacts, and your commitments; and much more! The iPhone is designed to be user-friendly, attractive, and functional. But it is capable of so much more than you think-don't you want to explore the possibilities? This book walks you through iOS 13 visually to help you stay in touch, get things done, and have some fun while you're at it! Get to know iOS 13 with 900 full-color screen shots Master the iPhone's basic functions and learn the latest features Customize your iPhone to suit your needs and get optimal performance Find the apps and services that can make your life easier The iPhone you hold in your hand represents the pinnacle of mobile technology and is a masterpiece of industrial design. Once you get to know it, you'll never be without it. Teach Yourself VISUALLY iPhone is your personal map for exploring your new tech companion.
Online resource; Title from title page (viewed February 26, 2020)
Keywords: iPhone (Smartphone); Mobile computing; Smartphones; iPhone (Téléphone intelligent); Informatique mobile; Téléphones intelligents